EFFECT OF A MIXTURE OF CADMIUM AND LEAD ON NITRATE AND PHOSPHATE REMOVAL BY THE DUCKWEED Lemna gibba - Aggoun, A.; Benmaamar, Z. (Annali di Botanica, 2019)
The purpose of the present study is to examine the effect of binary mixtures of the heavy metals, cadmium (Cd) and lead (Pb), on the assimilation of nitrate (NO3-) and orthophosphate (PO43-) from N and P-rich culture medium of the duckweed Lemna gibba. In binary mixtures, varied Cd concentrations (0.01, 0.1 and 1mgCd/L) were tested with 0.1 and 1 mgPb/L respectively. Experiments were run for 2, 4, 6 and 8 days. Results showed that in all treatments (Cd+Pb), orthophosphates concentration decreased markedly within the two days of initiating experiments. The highest phosphate removal efficiency is 89.39%, in the solutions containing a binary mixture of Pb at 0.1 mg/L combined with Cd mg/L on the fourth day and about 83% in a binary mixture of Pb and Cd at 1mg/L each metal. Nevertheless, nitrate removal was weak with time. The co-contamination of the plant culture medium with varied Cd + Pb concentrations has no effect on phosphate removal, as compared to the control. Additionally, Cd and Pb were removed from the medium and accumulated on Lemna gibba.